2016
DOI: 10.1155/2016/1872351
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Affect Functional Bioenergetic Traits in the Invasive Red Sea MusselBrachidontes pharaonis

Abstract: We investigated the functional trait responses to 5 nm metallic silver nanoparticle (AgNPs) exposure in the Lessepsian-entry bivalve B. pharaonis. Respiration rate (oxygen consumption), heartbeat rate, and absorption efficiency were evaluated across an 8-day exposure period in mesocosmal conditions. Basal reference values from not-exposed specimens were statistically compared with those obtained from animals treated with three sublethal nanoparticle concentrations (2 μg L−1, 20 μg L−1, and 40 μg L−1). Our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
3
2
0
Order By: Relevance
“…This latter aspect was also confirmed by Saggese et al [ 38 ] treating Red Sea mussel B. pharaonis with Ag-NPs. In this study, the lowest and highest doses of exposure could both increase the respiration rate of mussels compared to the controls and the middle dose groups.…”
Section: Resultssupporting
confidence: 76%
“…This latter aspect was also confirmed by Saggese et al [ 38 ] treating Red Sea mussel B. pharaonis with Ag-NPs. In this study, the lowest and highest doses of exposure could both increase the respiration rate of mussels compared to the controls and the middle dose groups.…”
Section: Resultssupporting
confidence: 76%
“…111,112 A similar oxygen consumption increase was reported in other aquatic species exposed to different NPs, e.g. , Perca fluviatilis exposed to AgNO 3 , 113 Brachidontes pharaonic exposed to Ag NPs, 114 Fundulus heteroclitus exposed to Cu NPs 115 and Apistogramma agassizii and Paracheirodon axelrodi exposed to Cu and CuO NPs. 111…”
Section: Resultssupporting
confidence: 77%
“…111 Gill structure damage can compromise Environmental Science: Nano Paper Environmental Science: Nano Paper respiratory gas exchange, increase energy demand for osmoregulation, and subsequently elevate oxygen consumption. 111,112 A similar oxygen consumption increase was reported in other aquatic species exposed to different NPs, e.g., Perca fluviatilis exposed to AgNO 3 , 113 Brachidontes pharaonic exposed to Ag NPs, 114 Fundulus heteroclitus exposed to Cu NPs 115 and Apistogramma agassizii and Paracheirodon axelrodi exposed to Cu and CuO NPs. 111…”
Section: Effect Of Ps and Ag Nanoparticles On Oxygen Consumptionsupporting
confidence: 77%
“…Impairment of physiological parameters related to bioenergetic functions after Ag NPs exposure were also demonstrated. In a study conducted by Saggese et al (2016), the authors observed significant effects on the average respiration rate of Brachidontes pharaonis exposed to low doses of Ag NPs (2, 20, 40 µg L -1 ) in mesocosm. Complex nonlinear dynamics were also detected as a function of the concentration level and time and heartbeat rates largely increased with no acclimation in animals exposed to the two highest levels with similar temporal dynamics.…”
Section: Enm Effectsmentioning
confidence: 98%